Determinants of bankruptcy probability in Indonesian rural banks - Chaerani Nisa; Tia Ichwani; Dewi Kurniawati; Ameilia Damayanti (Banks and Bank Systems, 2025)
This study investigates the key factors influencing the probability of bankruptcy among rural banks in Indonesia, concentrating on internal, industry-specific, and external factors. The study analyzes 1,391 conventional rural banks in Indonesia from 2019 to 2023, resulting in 6,919 bank-year observations. This study uses financial and regional macroeconomic data and applies a population-averaged logistic regression model on a balanced panel dataset. The results indicate that internal factors play a significant role in determining the probability of bankruptcy. In contrast, industry characteristics, which are competition and regulation, and external factors, such as economic growth, do not exhibit a substantial impact. Rural banks characterized by inadequate capital and low profitability are at a heightened risk of insolvency, exacerbated by a significant proportion of non-performing loans. Excessive liquidity paradoxically leads to insolvency, as it indicates the presence of underutilized assets, increasing the chance of failure. These findings confirm that policies encouraging underperforming rural banks to merge with solid rural banks are suitable. These strategies promote a more robust rural banking ecosystem and effective regulatory control by decreasing the number of rural banks. AcknowledgmentThis research was funded by Hibah BIMA Kemendikburistek, grant number 0008/LPPM/UP/VI/2024.